2017
DOI: 10.1071/py16135
|View full text |Cite
|
Sign up to set email alerts
|

Reducing recurrence of bacterial skin infections in Aboriginal children in rural communities: new ways of thinking, new ways of working

Abstract: Abstract.Reports from health workers, school staff and community members in rural NSW suggested that bacterial skin infections are a significant health issue for Aboriginal children and their families, affecting quality of life and contributing to poor school attendance. Current NSW treatment guidelines do not incorporate important sociocultural factors or ways of living in Aboriginal communities. The aim of this qualitative study was to gain a deeper understanding of the experience of parents and carers of Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Measuring potential under-recognition of skin infection at a patient and community level and exploring factors that contribute should be a focus of future studies. Certainly the phenomenon of normalisation has been described at the community level[21, 24] and may present a major barrier to health seeking and access to appropriate treatment in resource limited settings with endemic disease[25, 52]. It follows that any strategies to improve recognition and treatment of skin infection must consider and partner with the members of the communities which are affected[21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Measuring potential under-recognition of skin infection at a patient and community level and exploring factors that contribute should be a focus of future studies. Certainly the phenomenon of normalisation has been described at the community level[21, 24] and may present a major barrier to health seeking and access to appropriate treatment in resource limited settings with endemic disease[25, 52]. It follows that any strategies to improve recognition and treatment of skin infection must consider and partner with the members of the communities which are affected[21].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly the phenomenon of normalisation has been described at the community level[21, 24] and may present a major barrier to health seeking and access to appropriate treatment in resource limited settings with endemic disease[25, 52]. It follows that any strategies to improve recognition and treatment of skin infection must consider and partner with the members of the communities which are affected[21]. Moreover, ongoing efforts to address the social determinants which lead to the disproportionate load borne by people of Aboriginal ethnicity, particularly those living in remote communities, remain of great importance[8, 21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For Aboriginal and Torres Strait Islander peoples this message would be self-evident, and Maclean et al present evidence that interventions promoting expression of cultural identities have beneficial effects (MacLean et al 2017). Taking a community wide approach to address social determinants and strengthen cultural identity was more effective than narrow biomedical approaches in addressing youth suicide (Cox et al 2014), pyoderma (Thomas et al 2017), the content of health assessments (Spurling et al 2017), and food insecurity (Murray et al 2014). For example, in Queensland, McCalman et al found that support groups which promote social cohesion for Aboriginal men could lead to a variety of improvements including social and emotional wellbeing (McCalman et al 2010).…”
mentioning
confidence: 99%